Numerical studies of baroclinic instability - Elliott, S; Simon S. Elliott (1995)
﻿ This thesis describes two studies of baroclinic instability in a rotating fluid annulus subject to differential heating. The first part is concerned with the development of a time dependent axisymmetric numerical model. The model was formulated using the control volume finite element method and was designed to be as flexible as possible both in terms of the range of problems to be studied and the techniques used to study them. Details of these techniques are presented together with a discussion of their limitations and possible refinements and extensions which could be made. The second part of this thesis describes a numerical study of unstable normal mode perturbations which can develop on a prescribed mean state. The growth rate and structure of these modes are examined for various background states and the relevance of these results to laboratory measurements is discussed. Evidence is presented to suggest the possible presence of hitherto unobserved baroclinic weak waves in an internally heated annulus system.